Pembangunan Kesehatan Masyarakat Desa melalui Edukasi dan Skrining dalam Meningkatkan Perilaku Hidup Sehat - Asti Alifya; Etty Komariah Sambas; Yeli Yulianti; Silvya Nur Apni Oktavia; Sultan Fajar; Aulia Nurhabibah; Siska Kurnia; Risani Septiani; Ai Nuriyah; Sri Wahyuni Hardianti; Ranjib Abdul Aziz (LPMP Imperium, 2026)
Efforts to improve public health status can be achieved through health education and regular health screenings. Common health issues in the community, such as hypertension, diabetes mellitus, and eye health disorders, are often influenced by low levels of knowledge and poor healthy lifestyle practices. This community service program aimed to enhance public knowledge, attitudes, and behaviors regarding the prevention of hypertension and diabetes mellitus, as well as maintaining eye health. The program was conducted in RT 04/RW 08 Bantargedang, Kersanegara Village, Tasikmalaya, involving 40 respondents. The intervention methods included health counseling using leaflets and posters, along with basic health screenings consisting of blood pressure measurement, random blood glucose (RBG) tests, Body Mass Index (BMI) assessment, and eye health screenings. Evaluation was performed using pre-test and post-test questionnaires. There was a significant increase in knowledge, attitudes, and behaviors following the counseling. The average knowledge score increased from 73.18 to 87.05; the attitude score rose from 79.25 to 92.13; and the behavior score improved from 71.25 to 90.88. Health education and screenings proved to be effective in increasing public awareness and capacity to adopt a Clean and Healthy Lifestyle (CHL/PHBS).